Américo Jacomino (Canhoto): um estudo sobre os efeitos da mediação fonográfica na cultura do violão brasileiro - Manzoli, Felipe Pessin (2022)
In this work, we undertook an investigation into the effects of phonographic mediation in Brazilian’s guitar culture through study about the guitarist Américo Jacomino, the “Canhoto” (1889-1928). Moreover, there are two aspects considered: (1) Canhoto's relationship with phonography, a technological mediation that was established in the field of music in the first decades of the 20th century; (2) a musicological analysis of the specific musical traits of Canhoto's phonographic work that crystallized in the culture of the Brazilian guitar throughout the 19th century. XX. For this purpose, the theoretical framework of audiotactile musicology is used. This theory identifies the ways of forming music in cultures from a mediological and cognitive approach. Furthermore, it distinguishes “visual matrix” and “audiotactile matrix” mediation, and other references that study the impact of media in art and society. Thus, the starting point is the idea that phonographic mediation plays a fundamental role in recording and transmitting stylistic traits characteristic of the musical practice linked to the Brazilian guitar. Besides, through Canhoto's recordings, it is possible to recognize specificities of this creative process that have been perpetuated in the later style of Brazilian guitarists. As a result of our analysis, we evidenced in Canhoto's recorded work the existence of complex and aesthetically relevant structures, called groovemas, which are produced and inscribed as text in the work by the action of the body, and not from the traditional musical notation system, the score. This observation corroborates the study presented in the first part of the work on the practical method created by Canhoto, which offers clues about his pedagogical practice and even about his poetic program as a guitarist. The phonograms used in the analysis procedures were extracted from the historical recordings of “Viola minha Viola” and “Abismo de Rosas”, made by Canhoto. To identify and classify the forming particles of the groove, macrostructural and microstructural analyses, were applied, with the help of specialized software. In the case of “Abismo de Rosas”, we carried out analyzes in a comparative perspective on eleven recordings of the same piece, made by renowned guitarists in the history of the Brazilian guitar, in order to verify the ability to transmit characteristic aspects of Canhoto's expressiveness through technological mediation of recording. Finally, this research might facilitate the opening for new analysis perspectives and future research, expanding the understanding of the power of this resource studied.